Isolated Fetal Ventriculomegaly: Diagnosis and Treatment in the Prenatal Period - Mateusz Zamłyński; Olena Zhemela; Anita Olejek (MDPI AG, 2024)
Fetal ventriculomegaly (VM) is a defect of the central nervous system, typically diagnosed during the second-trimester ultrasound in fetuses with an atrial diameter (AD) of >10 mm. Non-isolated ventriculomegaly (NIVM) is heterogeneous in nature, coexisting with additional intracranial and/or extracranial malformations and genetic syndromes, resulting in an unfavorable prognosis for the further development of the child. Both the pregnancy management and counseling are dependent on the findings of combined ultrasound/MRI, genetic testing, and gestational age at diagnosis. The purpose of this review is to propose a hypothesis that diagnostic advancements allow to define the process of identification of the isolated forms of VM (IVM). Based on the evidence presented in the literature, we consider whether prenatal decompression for severe isolated VM (ISVM) is supported by the experimental trials and whether it might be implemented in clinical practice. Also, we describe the evolution of the diagnostic methods and expert opinions about the previously used prenatal decompression techniques for ISVM. In conclusion, we introduce the idea that fetal surgery centers have either reached or nearly reached the necessary level of expertise to perform such procedures. Endoscopic cystoventriculostomy (ETV) appears to be the most promising, as it is associated with minimal perinatal complications and favorable neurological outcomes in the neonatal period. Randomized trials with long-term neurodevelopmental follow-up of children who underwent prenatal decompression due to ISVM are necessary.